Trajectories of violence: the border experiences of peruvian women between Tacna (Peru) and Arica (Chile) - Lube Guizardi, Menara (2020)
The article discusses the strategies articulated by Peruvian women in the border area between Chile and Peru to confront the historical legitimations of gender violence in this territory. In Peru, their trajectories are marked by violations, labor exploitation, kidnapping and slave labor. In Chile, other violence and discrimination (labor, documentary, sexist aggressions) persist, being supported in a discourse on the ethnic-national inferiority of Peruvians. Thus, there is a tension between social legitimacy and legal illegality, and between agency and subordination as far as gender violence is concerned. Supported by ethnographic data, we will define this tension as a process that (re) inscribes, in the vital trajectories of women, disparate forms of marginalization and border crossing.